BUDGET AND CONTENT STRATEGY: AN EXPERIMENT ON DAILY SALES ON A SMALL FASHION ONLINE SHOP (The Indonesian Journal of Business Administration, 2021)
SMEs are faced with new business opportunities through online channels, i.e., social media. The online platform offers many advantages, especially for small businesses, to raise awareness, attract broader consumers, and eventually scale up the company. However, this opportunity also comes with a whole different challenge on how to optimize the platform. Many small businesses fail to overcome the new challenges due to their limitations, such as lack of financial and human resources. The purpose of this study is to examine the relationship between budget strategy and content strategy on the daily sales performance of an online fashion retail shop in Indonesia. By.yesya is used as an experimental object and analyzed using a quantitative research method through a lens of multivariate analysis (i.e. OLS regression). Using 1,637 daily sales observations, the result shows that the amount of budget allocation and the application of content strategy in the advertising material significantly increase its sales performance. One main conclusion is that this study provides a glimmer of enlightenment; there should be a reference whereby other businesses are keen to see how online advertising is sufficient to increase sales performance.Keywords: Advertising, Social Media, Budget, Content Strategy, Facebook, SME.